1994
DOI: 10.1128/aem.60.4.1121-1128.1994
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of competition in soil among 2,4-dichlorophenoxyacetic acid-degrading bacteria

Abstract: Competition among indigenous and inoculated 2,4-dichlorophenoxyacetic acid (2,4-D)-degrading bacteria was studied in a native Kansas prairie soil following 2,4-D additions. The soil was inoculated with four different 2,4-D-degrading strains at densities of 103 cells per g of soil; the organisms used were Pseudomonas cepacia DBO1(pJP4) and three Michigan soil isolates, strain 745, Sphingomonas paucimobilis 1443, and Pseudomonas pickettii 712. Following 2,4-D additions, total soil DNA was extracted and analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 17 publications
2
21
0
Order By: Relevance
“…Other work in our laboratory showed that transmissible plasmids are present in all of the strains of this group that have been tested (23). The group I strains grow well on 2,4-D and also appear to be selected by 2,4-D in the field, which is consistent with the competitiveness conferred by their related plasmid, pJP4 (15). Members of this group also degraded most other aromatic substrates tested.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Other work in our laboratory showed that transmissible plasmids are present in all of the strains of this group that have been tested (23). The group I strains grow well on 2,4-D and also appear to be selected by 2,4-D in the field, which is consistent with the competitiveness conferred by their related plasmid, pJP4 (15). Members of this group also degraded most other aromatic substrates tested.…”
Section: Discussionsupporting
confidence: 72%
“…In most previous studies, 2,4-D-degrading bacteria have been isolated by enrichment from undiluted environmental samples in broth cultures containing a high 2,4-D concentration. Under these conditions, strains belonging to hybridization group I are preferably isolated because of their rapid growth (15). This may also explain why most of the 2,4-D-degradative plasmids independently isolated from numerous Alcaligenes species exhibited high degrees of similarity to plasmid pJP4 in biophysical and genetic properties (6) and also why most of the 2,4-D-degrading bacteria isolated from various natural water samples exhibited surprising uniformity in their phenotypes, metabolism, and cell structure (1).…”
Section: Discussionmentioning
confidence: 99%
“…Reports now provide preliminary data on unculturable bacteria, allowing the extent of the total diversity in various environments to be better estimated (21,47,54). The techniques have, for example, made it possible to study alterations in the composition of soil microbial communities due to various disturbances (5,41), to identify specific indigenous populations (19,22) or specific functional genes (17,44), and to monitor the fate of microorganisms or genes released in the environment (8,33). They are also essential for addressing fundamental questions concerning the natural spread of genes via mechanisms such as conjugation, transformation, and transduction.…”
mentioning
confidence: 99%
“…Commercial 2, 4-Dichlorophenoxyacetic acid products are marketed as alkali salts, amine salts and ester formulations. Many micro-organisms, including the members of the Pseudomonas family, can degrade 2, 4-Dichlorophenoxyacetic acid (Ka and Tiedje 1994;Ka et al 1994aKa et al , 1994b. The structural gene tfdA from plasmid pJP4 encoding the first of the functional enzymes necessary for the transformation of chlorocatechols into 3-oxoadipate (Don and Pemberton 1981) has been used as a probe to detect bacterial populations with 2, 4-Dichlorophenoxyacetic acid degrading capability.…”
Section: 4-dichlorophenoxyacetic Acidmentioning
confidence: 99%
“…The structural gene tfdA from plasmid pJP4 encoding the first of the functional enzymes necessary for the transformation of chlorocatechols into 3-oxoadipate (Don and Pemberton 1981) has been used as a probe to detect bacterial populations with 2, 4-Dichlorophenoxyacetic acid degrading capability. In R. pickettii, homologous tfd genes have been shown to be plasmid borne (Ka et al 1994a). One R. pickettii isolate (designated 712) contains a 40AE9-kb plasmid that hybridizes to a 2, 4-Dichlorophenoxyacetic acid tfdA gene probe and shares the features in common with pKA2 from Variovorax paradoxus (formally Alcaligenes paradoxus) (Willems et al 1991).…”
Section: 4-dichlorophenoxyacetic Acidmentioning
confidence: 99%